The mechanism of traditional medicine in alleviating ulcerative colitis: regulating intestinal barrier function - Xu, Qiuyun; Yao, Yuan; Liu, Yongchao; Zhang, Jie; Mao, Liming (Frontiers in Pharmacology, 2023)
Ulcerative colitis (UC) is an idiopathic inflammatory disease mainly affects the large bowel and the rectum. The pathogenesis of this disease has not been fully elucidated, while the disruption of the intestinal barrier function triggered by various stimulating factors related to the host genetics, immunity, gut microbiota, and environment has been considered to be major mechanisms that affect the development of UC. Given the limited effective therapies, the treatment of this disease is not ideal and its incidence and prevalence are increasing. Therefore, developing new therapies with high efficiency and efficacy is important for treating UC. Many recent studies disclosed that numerous herbal decoctions and natural compounds derived from traditional herbal medicine showed promising therapeutic activities in animal models of colitis and have gained increasing attention from scientists in the study of UC. Some of these decoctions and compounds can effectively alleviate colonic inflammation and relieve clinical symptoms in animal models of colitis via regulating intestinal barrier function. While no study is available to review the underlying mechanisms of these potential therapies in regulating the integrity and function of the intestinal barrier. This review aims to summarize the effects of various herbal decoctions or bioactive compounds on the severity of colonic inflammation via various mechanisms, mainly including regulating the production of tight junction proteins, mucins, the composition of gut microbiota and microbial-associated metabolites, the infiltration of inflammatory cells and mediators, and the oxidative stress in the gut. On this basis, we discussed the related regulators and the affected signaling pathways of the mentioned traditional medicine in modulating the disruption or restoration of the intestinal barrier, such as NF-κB/MAPK, PI3K, and HIF-1α signaling pathways. In addition, the possible limitations of current studies and a prospect for future investigation and development of new UC therapies are provided based on our knowledge and current understanding. This review may improve our understanding of the current progression in studies of traditional medicine-derived therapies in protecting the intestinal barrier function and their roles in alleviating animal models of UC. It may be beneficial to the work of researchers in both basic and translational studies of UC.